Keragaman kasus patologi forensik di RSUP Prof. Dr. R. D. Kandou Manado dari sudut pandang SKDI 2012 periode Juli 2015-Juni 2016 - Tololiu, Charity C.; Kristanto, Erwin G.; Mallo, Nolla T.S. (e-CliniC, 2016)
Abstract: Forensic pathology is a study that focuses on determination of death causes by examining the corpse, especially for investigation of criminal cases and civil law cases. Knowledge and skills are needed for a doctor to get an accurate result of examination. Therefore, the general practicioners are required to master all the level of competence by the National Standard Competencies of Indonesian Medical Doctors 2012 (Standar Kompetensi Dokter Indonesia/SKDI). This study refered to Prof. Dr. R. D. Kandou Hospital as the main educational hospital for Medical Faculty of Sam Ratulangi University and also a tertiary health facility. This study was aimed to determine the diversity of cases in the Department of Forensic Pathology at Prof. Dr. R. D. Kandou Hospital from the viewpoint of National Standard Competencies of Indonesian Medical Doctors 2012 (Standar Kompetensi Dokter Indonesia/SKDI). This was a descriptive retrospective study. The result showed that the diversity of cases at Department of Pathology Forensic was 78% which was sufficient for standard competency requirements. Conclusion: Overall, Prof. Dr. R. D. Kandou Hospital is still eligible as the main educational hospital of Medical Faculty of Sam Ratulangi University. It is suggested to prolong the period of study in Forensic Department to increase the number of cases as well as to support the study with medical videos in order to increase the knowledge about the level 2 – competency cases.Keywords: forensic pathology, physician competence, SKDI 2012 Abstrak: Patologi Forensik adalah ilmu yang berkaitan dengan penentuan penyebab kematian melalui pemeriksaan pada jenazah, dilakukan terutama untuk membantu investigasi kasus kejahatan atau kasus perdata. Ilmu dan ketrampilan seorang dokter dibutuhkan agar hasil pemeriksaan akurat. Dokter umum diwajibkan menguasai seluruh tingkat kompetensi dalam buku Standar Kompetensi Dokter Indonesia 2012. Penelitian merujuk pada RSUP Prof. Dr. R. D Kandou sebab rumah sakit tersebut merupakan faskes tersier yang juga merupakan rumah sakit pendidikan utama Fakultas Kedokteran UNSRAT. Penelitian ini bertujuan untuk mengetahui keragaman kasus Patologi Forensik di RSUP Prof. Dr. R. D. Kandou Manado dari sudut pandang SKDI 2012 periode Juli 2015 – Juni 2016. Jenis penelitian ialah deskriptif retrospektif. Hasil penelitian memperlihatkan bahwa 78% keragaman kasus di bagian Forensik mencukupi untuk kebutuhan standar akreditasi. Simpulan: Secara keseluruhan RSUP Prof. Dr. R. D. Kandou masih layak sebagai rumah sakit pendidikan utama Fakultas Kedokteran Universitas Sam Ratulangi. Disarankan memperpanjang masa studi di Bagian Forensik agar dapat meningkatkan jumlah kasus dan pembelajaran dengan video medis dalam meningkatkan pengetahuan tentang kasus yang memiliki tingkat kompetensi 2. Kata kunci: patologi forensik, kompetensi dokter, SKDI 2012